Induction of autophagy protects against extreme hypoxia-induced damage in porcine embryo. Issue 4 (April 2021) - Lee, Mun-Hyeong; Jeong, Pil-Soo; Sim, Bo-Woong; Kang, Hyo-Gu; Kim, Min Ju; Lee, Sanghoon; Yoon, Seung-Bin; Kang, Philyong; Park, Young-Ho; Kim, Ji-Su; Song, Bong-Seok; Koo, Deog-Bon; et al.
Abstract : In the mammalian female reproductive tract, physiological oxygen tension is lower than that of the atmosphere. Therefore, to mimic in vivo conditions during in vitro culture (IVC) of mammalian early embryos, 5% oxygen has been extensively used instead of 20%. However, the potential effect of hypoxia on the yield of early embryos with high developmental competence remains unknown or controversial, especially in pigs. In the present study, we examined the effects of low oxygen tension under different oxygen tension levels on early developmental competence of parthenogenetically activated (PA) and in vitro -fertilized (IVF) porcine embryos. Unlike the 5% and 20% oxygen groups, exposure of PA embryos to 1% oxygen tension, especially in early-phase IVC (0–2 days), greatly decreased several developmental competence parameters including blastocyst formation rate, blastocyst size, total cell number, inner cell mass (ICM) to trophectoderm (TE) ratio, and cellular survival rate. In contrast, 1% oxygen tension did not affect developmental parameters during the middle (2–4 days) and late phases (4–6 days) of IVC. Interestingly, induction of autophagy by rapamycin treatment markedly restored the developmental parameters of PA and IVF embryos cultured with 1% oxygen tension during early-phase IVC, to meet the levels of the other groups. Together, these results suggest that the early development of porcine embryos depends on crosstalk between oxygen tension and autophagy. Future studies of this relationship should explore the developmental events governing early embryonic development to produce embryos with high developmental competence in vitro .